Financial Attention - Sicherman, Nachum; Loewenstein, George; Seppi, Duane J.; Utkus, Stephen P. (Review of Financial Studies, 2016)
This paper investigates financial attention using novel panel data on daily investor online account logins. We find support for selective attention to portfolio information. Account logins fall by 9.5% after market declines. Investors also pay less attention when the VIX volatility index is high. The level of attention and the attention/return correlation are strongly related to investor demographics (gender, age) and financial position (wealth, holdings). Using a new statistical decomposition, we show how aggregate and individual household trading are related to investor attention. Received October 31, 2014; accepted July 29, 2015 by Editor David Hirshleifer.